2017
DOI: 10.1186/s12864-017-4254-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness of Vibrio cholerae isolates within and between households during outbreaks in Dhaka, Bangladesh

Abstract: BackgroundHousehold contacts of cholera patients have a 100 times higher risk of developing a cholera infection than the general population. To compare the genetic relatedness of clinical and water source Vibrio cholerae isolates from cholera patients’ households across three outbreaks, we analyzed these isolates using whole-genome-sequencing (WGS) and multilocus variable-number tandem-repeat analysis (MLVA).ResultsThe WGS analyses revealed that 80% of households had source water isolates that were more closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Spatiotemporal analyses of cholera in endemic and epidemic settings have instead demonstrated clusters of cases within 200m distances of case-households during the first five days after index cases present with symptoms [48][49][50], and a 100-fold higher risk of household contacts of cases to contract the disease compared to those outside the household [43,[51][52][53][54]. Research on the genomics of cholera transmission has also demonstrated strong phylogenetic similarities among same-household cases [43,[55][56][57][58], and a recent paper found 80% of transmission occurs between people who share a household [55]. Accordingly, faecal-oral transmission of cholera within the household, predominantly through the human-to-human transmission pathway, may far better explain the propagated and explosive nature of cholera outbreaks than community-level transmission from exposure to environmental point sources and environment-to-human transmission [27,29,45,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Spatiotemporal analyses of cholera in endemic and epidemic settings have instead demonstrated clusters of cases within 200m distances of case-households during the first five days after index cases present with symptoms [48][49][50], and a 100-fold higher risk of household contacts of cases to contract the disease compared to those outside the household [43,[51][52][53][54]. Research on the genomics of cholera transmission has also demonstrated strong phylogenetic similarities among same-household cases [43,[55][56][57][58], and a recent paper found 80% of transmission occurs between people who share a household [55]. Accordingly, faecal-oral transmission of cholera within the household, predominantly through the human-to-human transmission pathway, may far better explain the propagated and explosive nature of cholera outbreaks than community-level transmission from exposure to environmental point sources and environment-to-human transmission [27,29,45,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that domestic domain transmission is important, but it is difficult to infer its role relative to public transmission from case-control studies alone. However, other research using different methods, such as cohort designs [103][104][105][106][107], mathematical modelling [17,24,108], non-case-control epidemiological methods [103,109,110], environmental analysis [111] and molecular epidemiology [21,112,113], reinforce the importance of domestic transmission. One cohort study estimated the attributable risk from household transmission to be two to four times greater in magnitude than public transmission over short time scales [103].…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise comparisons were made of the number of allele differences in the five locus genotype (e.g. this would be one if a single locus varied) [ 17 ]. Fisher’s exact, paired t-tests, and permutation tests were computed using SAS (version 9.3) to analyze MLVA data.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study found that V . cholerae isolates with the same MLVA genotype had significantly fewer pairwise differences by whole genome sequencing (WGS) compared to isolates with different MLVA genotypes [ 17 ]. This is consistent with findings from Rashid et al which found that isolates closely related by MLVA had significantly fewer nucleotides differences by WGS than isolates distantly related by MLVA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation